2007
DOI: 10.1021/om0608713
|View full text |Cite
|
Sign up to set email alerts
|

Ring Expansion of a Platinacyclopropane to a Platinacyclopentane by Double Insertion of Isocyanides into Pt−C Bonds

Abstract: A platinum isocyanide complex bearing a η2-TCNE ligand, (η2-TCNE)Pt(η-CNC6H3-2,6-Me2)2 (1), was synthesized, and its crystallographic study revealed the coordination mode of the η2-TCNE ligand to be a typical metallacyclopropane extreme, in which back-donation from metal to TCNE contributes primarily to the stabilization of 1. Treatment of 1 with 2 equiv of CNC6H3-2,6-Me2 resulted in ring expansion of the platinacyclopropane by insertion of CNC6H3-2,6-Me2 into each Pt−C bond of the metallacycle, leading to for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
16
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 56 publications
(31 reference statements)
6
16
0
Order By: Relevance
“…Recent examples include Ru­(η 1 -tcne)­{NBu t C­(mes)­NBu t }­Cp*, trans -[{Ru­(PPh 3 ) 2 Cp} 2 (μ-tcne)] 2+ , and [{Fe­(CO) 2 Cp} 4 (μ 4 -tcne)] n + ( n = 3, 4) . Metal π complexes were first reported by Baddley, who prepared Pt­{η 2 -C 2 (CN) 4 }­(PPh 3 ) 2 and showed conversion of this complex to trans -Pt­(CN)­{C­(CN)C­(CN) 2 }­(PPh 3 ) 2 . , Many related compounds have since been prepared, especially for the later transition metals, such as M­(CO) 5 (η 2 -tcne) (M = Cr, W), Ru­(η 2 -tcne)­(NRCR′NR)­Cp*, and M­(η 2 -tcne)­(L) 2 (M = Ni, Pd, Pt, L = CNAr), and aspects of the coordination chemistry of tcne and physical properties of the resulting complexes have also been reviewed. …”
Section: Introductionmentioning
confidence: 99%
“…Recent examples include Ru­(η 1 -tcne)­{NBu t C­(mes)­NBu t }­Cp*, trans -[{Ru­(PPh 3 ) 2 Cp} 2 (μ-tcne)] 2+ , and [{Fe­(CO) 2 Cp} 4 (μ 4 -tcne)] n + ( n = 3, 4) . Metal π complexes were first reported by Baddley, who prepared Pt­{η 2 -C 2 (CN) 4 }­(PPh 3 ) 2 and showed conversion of this complex to trans -Pt­(CN)­{C­(CN)C­(CN) 2 }­(PPh 3 ) 2 . , Many related compounds have since been prepared, especially for the later transition metals, such as M­(CO) 5 (η 2 -tcne) (M = Cr, W), Ru­(η 2 -tcne)­(NRCR′NR)­Cp*, and M­(η 2 -tcne)­(L) 2 (M = Ni, Pd, Pt, L = CNAr), and aspects of the coordination chemistry of tcne and physical properties of the resulting complexes have also been reviewed. …”
Section: Introductionmentioning
confidence: 99%
“…Isocyanides have been widely applied to construct various nitrogen heterocyclic compounds due to their superior capability to rapidly create molecular diversity, however, most reported achievements mainly focus on the utility of isocyanides single insertion for the synthesis of nitrogen-containing compounds . Only a few examples of metal-catalyzed double isocyanides insertion have been reported . For example, in 2015, Tu and Jiang disclosed a palladium-catalyzed double isocyanide insertion–cyclization between 2-haloanilines and isocyanides to form 3-iminoindol-2-amines (Scheme a).…”
Section: Introductionmentioning
confidence: 99%
“…The principal motivation for this research is a remarkable recent experimental discovery in the laboratory of Nagashima . Via a variable-temperature NMR spectroscopy and several other probe techniques, the Japanese group reported that the group 10 metal isocyanide complexes bearing a η 2 -TCNE ligand, (η 2 -TCNE)Ni(η-CNC 6 H 3 -2-6-Me 2 ) 2 ( 1 ), (η 2 -TCNE)Pd(η-CNC 6 H 3 -2-6-Me 2 ) 2 ( 2 ), and (η 2 -TCNE)Pt(η-CNC 6 H 3 -2-6-Me 2 ) 2 ( 3 ), were synthesized and characterized structurally . In particular, they found that the coordination mode of the η 2 -TCNE ligand is a typical metallacyclopropane extreme, in which back-donation from Pt to TCNE contributes primarily to the stabilization of 3 .…”
Section: Introductionmentioning
confidence: 99%